Research Progress of Traditional Chinese Medicine in the Prevention and Treatment of Postoperative Complications of Anal and Intestinal Diseases - Yang, Suwen; Feng, Qunhu (Journal of Contemporary Medical Practice, 2025)
Anal and intestinal diseases are prevalent in daily life and are often treated with surgical procedures. However, multiple postoperative symptoms such as infection, incontinence, bleeding, pain and swelling can have a significant impact on the patient's postoperative recovery and daily life. Chinese medicine has accumulated rich experience in the treatment of postoperative complications of rectal and intestinal diseases, with the unique advantages of simplicity, fewer side effects and high efficacy. The main objective of this study was to investigate the use of Chinese medicine in the prevention and treatment of anal and intestinal diseases in terms of postoperative complications.